Etude et Réalisation d’un Tracker solaire autopiloté Commande via une carte Arduino - خلوط, عبد الرحيم; خلوط, أحمد (University of El Oued جامة الوادي, 2018)
يمكن تنفيذ مجموعة الطاقة الشمسية للإشعاع الشمسي بواسطة أنظمة ضوئية بطرق عديدة: في اتجاه أفقي ثابت ، على مستوى مائل إلى خط العرض للمكان ، على مستوى أمثل أو في اتجاه طبيعي. والهدف من عملنا هو تصميم وتنفيذ نظام تتبع الشمس في محورين (الارتفاع والوقت) من أجل تحسين وزيادة كمية الطاقة التي تنتجها النظم الكهربائية الضوئية. النمذجة ثلاثية الأبعاد ذلك باستخدام سوليدووركس البرمجيات، ونحن نستخدم متحكم (اردوينو (للتحكم في النظام لدينا لضمان التوجه الطبيعي للشمس على الألواح باستخدام أربعة أجهزة استشعار للمقاومة الضوئية المتغيرة . وفي الاخير ، تم إجراء مقارنة ضد لوحة شمسية ثابتة بنفس الخصائص ، مع تقييم أداء جهاز تتبع الطاقة الشمسية. Energy collection of solar radiation by photovoltaic systems can be effected in several ways: in a fixed horizontal orientation, on a plane inclined to the latitude of the place, on an optimal plane or in a normal orientation. The goal of our work is a design and implementation of a two-axis sun tracking system (Altitude and Hourly) to optimize and increase the amount of power produced by photovoltaic systems. A 3D modeling using SolidWorks software, and we use the microcontroller (ARDUINO UNO R3) to control our system to ensure a normal orientation of the sun on the panel using four Light Dependent resistor sensors (LDR). Finally, a comparison was made against a fixed solar panel with the same characteristics, with a solar Tracker performance rating.
مذكرة ماسترهندسة ميكانيكية تخصص إلكتروميكانيك
Keywords: Solar Tracker, Photovoltaics, Solar Energy, Arduino.; ماكنة متزامنة ذات مغانط دائمة، , تعديل عرض النبضة ، التحكم بتوجيه التدفق